Dynamic deformation and meso-structure of coarse-grained saline soil under cyclic loading with freeze-thaw cycles - Wan, Qi; Yang, Xiaohua; Wang, Rui; Zhu, Zhiheng (Frontiers in Earth Science, 2024)
The cumulative deformation properties of subgrade soil under cyclic traffic loads are critical for optimizing pavement structure design and ensuring long-term highway structural performance. To investigate the coupling effect of freeze-thaw cycles and cyclic loads on the cumulative deformation behaviors and meso-structure of coarse-grained saline soil (CGSS) subgrade filling in high-cold areas, this study conducted dynamic triaxial tests and computed tomography (CT) scanning on the CGSS under different working conditions. The research analyzed the dynamic deformation development and damage evolution under varying freeze-thaw cycles and load amplitudes. The research results show that the cumulative deformation behavior of CGSS under cyclic loading is relatively sensitive to the freeze-thaw process. The cumulative dynamic strain increases as the freeze-thaw cycles, with a critical freeze-thaw cycle number of five. The stable cumulative dynamic strain curve has a threestage structure under semi-log coordination, with critical loading cycles of 20 and 1000. After 10-100 loading cycles, the cumulative strain curve quickly shows failure. The CGSS's low density and pore regions greatly increase after a freeze-thaw cycle. The increase in dynamic stress amplitude has a significant impact on the bonding between soil particles and crystalline salts. The coupling effect of the freeze-thaw cycle and dynamic activity leads to more visible deterioration of the soil structure, resulting in variations in CT values within the scanning layer in the final state.